Doxing as A Threat to Freedom of Speech: A Juridical Review of Protection against The Dissemination of Personal Data on The Internet - Della Dearista Axelia; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2025)
Digital development not only brings a positive impact on life but raises various challenges regarding privacy and data security, one of which is doxing. The phenomenon of doxing, which is the disclosure of a person's personal information without permission, has become a serious threat to freedom of speech on the internet. The purpose of this research is to examine the impact of doxing on freedom of speech on the internet and analyzing the types of legal protection available to doxing victims in Indonesia based on the Personal Data Protection Law and the Electronic Information and Transaction Law. This research employs a normative juridical method, namely analyzing various legal regulations relating to doxing, namely Law No. 27 of 2022 on Personal Data Protection and Law No. 1 of 2024 about the Second Amendment to Law No. 11 of 2008 on Electronic Information and Transactions. This research uses secondary data consisting of primary, secondary, and tertiary legal materials with qualitative descriptive data analysis techniques that produce data that is systematically organized to describe the phenomenon of doxing. The results show that doxing inhibits freedom of speech because victims often experience intimidation, social pressure, and physical threats. The Personal Data Protection Law and Electronic Information and Transaction Law provide regulations for personal data and sanctions for doxing perpetrators. However, these regulations still need to be strengthened, increase public awareness, and more effective legal efforts in handling doxing cases.